2023
DOI: 10.1136/bmjresp-2022-001528
|View full text |Cite
|
Sign up to set email alerts
|

Lung function and cognitive ability in children: a UK birth cohort study

Abstract: BackgroundDecreased adult lung function is associated with subsequent impairment in cognition. A similar relationship in early life could be of great policy importance, since childhood cognitive ability determines key adult outcomes, including socioeconomic status and mortality. We aimed to expand the very limited data available on this relationship in children, and hypothesised that reduced lung function would be longitudinally associated with decreased cognitive ability.MethodsLung function was measured at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…In the current study, we incorporated the general intelligence score variable as part of our analysis, given that several previous studies have demonstrated an association between intelligence and lung function (Taylor et al 2005;Suglia et al 2008;Vasilopoulos et al 2015;Grenville et…”
Section: Ozone Exposure Assessment Metricsmentioning
confidence: 99%
“…In the current study, we incorporated the general intelligence score variable as part of our analysis, given that several previous studies have demonstrated an association between intelligence and lung function (Taylor et al 2005;Suglia et al 2008;Vasilopoulos et al 2015;Grenville et…”
Section: Ozone Exposure Assessment Metricsmentioning
confidence: 99%